Green Synthesis of Reduced Graphene Oxide Using Lime Juice Reductor From Citrus aurantifolia - Said Ali Akbar; Fitriya Nanda; Nispi Mawaddah; Mima Yuriati (Elkawnie, 2019)
In this study, the reduced graphene oxide (rGO) synthesized by using lime juice as an environmentally friendly reducing agent and inexpensive cost. The synthesis was carried out by oxidizing graphite with the Hummer method to form graphene oxide (GO) was formed, then the GO was reduced by using lime as the natural reducing agent. X-ray analysis shown a vital diffraction pattern for graphite at 2θ = 26.4°, for graphene oxide appears around 2θ = 10° and 43o, and rGO at 2θ = 23.8°. Furthermore, the infrared spectrum of the three samples showed the peak of the hydroxyl group at 3412 cm-1, which appeared on graphene oxide, but was not observed in rGO. The vibrational mode of carbonyl (C=O) at 1723 cm-1 was also observed with high intensity on graphene oxide. This information showed that GO has a large number of oxygen-containing groups. Then, in the dissolution test shown that the GO was more soluble in polar solvents such as water than ethanol.